Razvoj i organizacija huckepack prijevoza u Europi - Luketić, Mijo (Promet - Traffic&Transportation, 2012)
Piggy back technology of freight rail transport has particularly been invigorated .by the second world energy crisis of 1978. For purposes of relieving individual road routes, better utilization of rail infrastructure, reasons of environmental protection, lower costs, higher speed and safety of transport, the EEC supports financially the development of this aspect of transport technology. This paper deals with the existing organization/management of piggy-back transport in Europe with particular reference to the indices of efficiency of the German Society for Transport of Road Vehicles by Rail entitled ’Kombiverkehr A. G.’. Through identification of the forwarding agent as the organizer of shipment and delivery of goods by this technology the author refers us to the indispensability of this legal entity which as an entrepreneur acts on behalf of the business organization on completion of transport to satisfaction of the party providing and the party using this type of transport service.